Zakat, Infaq, dan Wakaf: Instrumen Distribusi Kekayaan dalam Ekonomi Mikro Islam - Nabila Putri Wirani; Zhafira Syaifani Siregar (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2025)
Economic distribution is one of the important topics in Islamic economics because it is related to the equality and welfare of the community. This article discusses distribution instruments from the point of view of capitalist and Islamic economics. Capitalism popularized by Adam Smith emphasized individual freedom in asset ownership, but it often led to inequality and poverty. In contrast, Islamic economics emphasizes justice and the equitable distribution of wealth according to religious principles. This study uses a qualitative descriptive method with a literature review. This research reaches the conclusion that an Islamic economic system should be established, which emphasizes the value of justice in property as well as human freedoms and actions in accordance with religious teachings.